2009
DOI: 10.1186/1743-8977-6-23
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of nano/microparticles in in vitro micronuclei, in vivo comet and mutation assay systems

Abstract: Background: Recently, manufactured nano/microparticles such as fullerenes (C 60 ), carbon black (CB) and ceramic fiber are being widely used because of their desirable properties in industrial, medical and cosmetic fields. However, there are few data on these particles in mammalian mutagenesis and carcinogenesis. To examine genotoxic effects by C 60 , CB and kaolin, an in vitro micronuclei (MN) test was conducted with human lung cancer cell line, A549 cells. In addition, DNA damage and mutations were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 51 publications
2
65
1
Order By: Relevance
“…In our study, the comet assay mean found in the group non-exposed to asbestos was 11 ± 2 AU. This is within the range found in the literature in several populations, reinforcing the fact that there was a statistically significant difference in DNA damage levels between the two groups, with the implication that these results were caused by exposure to asbestos [18,[28][29][30].…”
Section: Group Exposed To Asbestossupporting
confidence: 87%
“…In our study, the comet assay mean found in the group non-exposed to asbestos was 11 ± 2 AU. This is within the range found in the literature in several populations, reinforcing the fact that there was a statistically significant difference in DNA damage levels between the two groups, with the implication that these results were caused by exposure to asbestos [18,[28][29][30].…”
Section: Group Exposed To Asbestossupporting
confidence: 87%
“…In both studies, however, the bone marrow was not exposed to C60 directly. A recent report showed that intratracheal instillation of C60 increased both mutation frequency (gpt assay) and DNA damage (comet assay) in the lung (3). From the mutation spectra, it was suggested that oxidative DNA damage might be involved in mutagenicity of C60 (3).…”
Section: Discussionmentioning
confidence: 99%
“…Reports on the in vivo genotoxicity of C60, however, are con‰icting. It was reported that intratracheal instillation of C60 increased both mutation frequency detected by gpt-assay and DNA damage detected by comet assay in lung (3). Nevertheless another group showed that treatment with C60 by gavage has no genotoxical eŠect in ICR mice, using in vivo micronucleus test in bone marrow cells (4).…”
Section: Introductionmentioning
confidence: 99%
“…The MN test was carried out as described previously (Totsuka et al, 2009). Briefly, human lung carcinoma A549 cells and Chinese hamster ovary (CHO) AA8 cells obtained from the RIKEN Cell Bank (Wako, Japan) were cultured in Eagle's minimum essential medium (Nissui Pharmaceutical Co. Ltd., Tokyo, Japan) supplemented with 10% fetal bovine serum (JRH Biosciences, Lenexa, KS, USA) at 37ºC in a 5% CO 2 atmosphere.…”
Section: Micronucleus Testmentioning
confidence: 99%